The moral minefield: Legal and social Issues of tobacco and liquor marketing - Diane Sacks; R. Abratt (South African Journal of Business Management, 1986)
This article focuses on the liquor and tobacco industries. These two industries were chosen because they have been catapulted into the foreground of the societal marketing polemic as a result of the widespread agreement that the consumption of their products can cause serious damage to personal and social welfare. The legal and social context In which tobacco and liquor products are marketed internationally and in South Africa are discussed. Some general conclusions are drawn from this review which will have implications not only for the two industries involved, but society as a whole.
Keywords: 650